Characterization of acute myeloid leukemia with del(9q) – Impact of the genes in the minimally deleted region. (January 2019) - Naarmann-de Vries, Isabel S.; Sackmann, Yvonne; Klein, Felicitas; Ostareck-Lederer, Antje; Ostareck, Dirk H.; Jost, Edgar; Ehninger, Gerhard; Brümmendorf, Tim H.; Marx, Gernot; Röllig, Christoph; Thiede, Christian; Crysandt, Martina
Highlights: The mimimal deleted region (MDR) in AML del(9q) was confirmed in 31 patient samples. Expression of the MDR genes is reduced in del(9q) compared to normal karyotype samples. Mutation of CEBPA in del(9q) results in restored MDR gene expression. Our data indicate a link between the MDR gene HNRNPK and its target CEBPA . Abstract: Acute myeloid leukemia is an aggressive disease that arises from clonal expansion of malignant hematopoietic precursor cells of the bone marrow. Deletions on the long arm of chromosome 9 (del(9q)) are observed in 2% of acute myeloid leukemia patients. Our deletion analysis in a cohort of 31 del(9q) acute myeloid leukemia patients further supports the importance of a minimally deleted region composed of seven genes potentially involved in leukemogenesis: GKAP1, KIF27, C9ORF64, HNRNPK, RMI1, SLC28A3 and NTRK2 . Importantly, among them HNRNPK, encoding heterogeneous nuclear ribonucleoprotein K is proposed to function in leukemogenesis. We show that expression of HNRNPK and the other genes of the minimally deleted region is significantly reduced in patients with del(9q) compared with normal karyotype acute myeloid leukemia. Also, two mRNAs interacting with heterogeneous nuclear ribonucleoprotein K, namely CDKN1A and CEBPA are significantly downregulated. While the deletion size is not correlated with outcome, associated genetic aberrations are important. Patients with an additional t(8;21) show a good prognosis. RUNX1 - RUNX1T1, which emerges from the t(8;21) leads to transcriptional down-regulation of CEBPA . Acute myeloid leukemia patients with mutations in CEBPA have a good prognosis as well. Interestingly, in del(9q) patients with CEBPA mutation mRNA levels of HNRNPK and the other genes located in the minimally deleted region is restored to normal karyotype level. Our data indicate that a link between CEBPA and the genes of the minimally deleted region, among them HNRNPK contributes to leukemogenesis in acute myeloid leukemia with del(9q).